Avaliação in vitro de dentifrícios fluoretados e suplementados com HMP sobre a erosão do esmalte - Vilha, Thiago Aragaki [UNESP] (2013)
The aim of the present study was to evaluate the in vitro effect of dentifrices with different fluoride concentrations associated with HMP (sodium hexametaphosphate) on dental erosion. Bovine enamel blocks (n=72) were selected after polishing and surface hardness analysis (initial SH). Then, they were randomized into 6 groups (n=12) according to the dentifrice used: placebo, 1,100 μg F/g, 5,000 μg F/g, 500 μg F/g with 1% of HMP, 1,100 μg F/g with 2,2% of HMP and 5,000 μg F/g with 10% of HMP. Blocks were submitted for a period of 7 days to erosive challenges 4 x a day (citric acid solution, 0.04M, pH 3.2) during 5 minutes, following they were immediately treated with the respective dentifrice (slurry 1:3) for 15 seconds. There was a 2 hour interval between each erosive challenge/treatment. Blocks were analyzed by profilometry and surface hardness analysis. The results were analyzed by ANOVA, followed by Bonferroni (surface hardness) and Student- Newman-Keuls (profilometry) tests (p<0.05). The dentifrice containig 500 μg F/g with 1% promoted statistically similar enamel wear when compared to the 5,000 μg F/g product and it was significantly lower compared to the other groups (p<0.05). Regarding the surface hardness, the use of dentifrices containing 1100 μg F/g and 5000 μg F/g led to higher values, followed by 5,000 μg F/g with 10%HMP, 1,100 μg F/g with 2.2%HMP, 500 μg F/g with 1%HMP and placebo (p<0.05). It was concluded that the dentifrice 500 μg F/g supplemented with 1% HMP led to a higher protective effect when submitted to the erosive challenges and presented similar enamel wear to the 5000 μg F/g dentifrice